ANALISIS KUALITAS PELAYANAN DAN KENYAMANAN TEMPAT TERHADAP KEPUASAN PELANGGAN PADA HOTEL LOTUS GARDEN DAN RESTAURAN KEDIRI - Deswanda, Nantaskia Herni; Ichsannudin, Ichsannudin (Universitas Nusantara PGRI Kediri, 2022)
At the Lotus Garden Hotel and Kediri Restaurant, the purpose of this study is to investigate and investigate the impact of the quality of service and the comfort of the site on customer satisfaction. In this study, quantitative research is used in the form of the distribution of questionnaires to customers of the Kediri Restaurant and the Lotus Garden hotel. The goal of the study is to investigate the factors of customer satisfaction that are related to service quality and the comfort of the environment. Empirical study with the findings presented in the form of numbers is known as quantitative research. This study's data analysis made use of descriptive statistical analysis, data quality testing, and effect testing, all performed with the software program SPSS. According to the findings, the level of customer satisfaction at both the Lotus Garden Hotel and the Kediri Restaurant is significantly impacted by a number of factors, including the friendliness of the staff and the ambience of the location.